RELASI PEMASARAN DAN KEPERCAYAAN KONSUMEN TERHADAP LOYALITAS KONSUMEN - Kotimah; Aldona Olivia Zanuary; Yongki Adi Septiawan (LPPM INSTITUT AGAMA ISLAM HASANUDDIN PARE, 2024)
The background of this study aims to determine the relationship between consumer trust on satisfaction and customer loyalty. In this case, efforts to increase trust are very important and influential in terms of purchasing decisions. This type of research uses qualitative methods with several sources related to relationship marketing and consumer trust. The results of this study indicate that the relationship between trust and consumer loyalty will increase goods and services companies to obtain greater profitability.